Fenomena Ikumen sebagai Salah Satu Perubahan Peran dan Identitas Ayah dalam Masyarakat Jepang Modern - Iis Muhayaroh (Lingua Cultura, 2015)
Article focused on the changes of father’s role within modern society due to social changes that was called ikumen. Ikumen is a social change that happens in the father’s role and identity in Japan in which now is appears a type of father who enjoys caring for children while working. Ikumen itself was made by media, and then it was supported by the government. The purpose of this research was to analyse the changes of father’s role and identity in Japan using Social Change theory by Anthony Giddens. This research applied qualitative method and by interviewing six ikumen who were members of NPO (Non Profit Organization) Fathering Japan. The research finds out that right now there have been many fathers who have desire to put family first. It is proven by the amount of fathers who have taken paternal leave in Japan.